Cultural Value Diversity: Influence towards Multicultural Teamwork Performance among Restaurant Employees - Zahidah Ab-Latif; Asilah Abdul Mutalib; Zalina Ismail; Fazhana Ismail; Shaibatul ' Islamiah Che Man (Journal of Vocational Education Studies, 2020)
Malaysia currently has a diverse workforce, relying on foreign workers in the hospitality industry. This study tested a conceptual model to investigate the role of specific cultural diversity value in influencing multicultural teamwork performance. A self-administered questionnaire was conducted in casual ethnic restaurants in Malaysia. The findings revealed that the three diversity dimensions of collectivism, determinism, and orientation each had distinctive effects on productivity and/or cooperation. This study offers new insights on cultural value diversity and multicultural teamwork performance at a dimensional level thus provides rigid answer for the argument from previous scholars. In addition, by providing the current phenomena in workforce industry, this study helps the restaurant managers to prepare with strategic management on handling diversity among multicultural team.